Association between Body Composition Parameters and Heart Rate in a Sample of Adolescents with Anorexia Nervosa. Issue 3 (March 2023) - Denhardt, Brenna N.; Sobalvarro, Sarah E.; Reese, Jasmine M.; Parton, Jason; Ellis, Amy
Abstract : Anorexia nervosa can result in severe medical complications and death. This article provides a brief overview of how body composition parameters in patients with anorexia nervosa could affect the risk of low heart rate and the potential need for medical stabilization. Abstract: Objectives: Eating disorders affect the physical and mental health of millions of Americans. Body composition trends in relation to heart rate in adolescents with eating disorders remain understudied. The aim of the present study was to determine whether body composition parameters (percent body fat, percent skeletal muscle mass) are correlated with heart rate in a sample of adolescents with anorexia nervosa. Methods: This study included patients 11 to 19 years old who presented to an outpatient eating disorder clinic (N = 49). Patients underwent bioelectrical impedance analysis to estimate body composition parameters. Descriptive statistics, linear regression, and paired t tests were used to evaluate the data. Results: Heart rate was inversely associated with percent skeletal muscle mass ( P < 0.001) and positively associated with percent body fat ( P = 0.001). Patients demonstrated significant improvements in weight, body mass index percentile, skeletal muscle mass, percent body fat, and heart rate when comparing results at the first and last visits ( P < 0.01). Conclusions: Overall, there was an inverse relation between percent skeletal muscle mass and heart rate and a positive association between body fat and heart rate. Our study demonstrates the importance of assessing percent body fat and skeletal muscle mass rather than weight or body mass index alone in adolescents with eating disorders.